2015
DOI: 10.1093/nar/gkv900
|View full text |Cite|
|
Sign up to set email alerts
|

Guanine quadruplex structures localize to heterochromatin

Abstract: Increasing amounts of data support a role for guanine quadruplex (G4) DNA and RNA structures in various cellular processes. We stained different organisms with monoclonal antibody 1H6 specific for G4 DNA. Strikingly, immuno-electron microscopy showed exquisite specificity for heterochromatin. Polytene chromosomes from Drosophila salivary glands showed bands that co-localized with heterochromatin proteins HP1 and the SNF2 domain-containing protein SUUR. Staining was retained in SUUR knock-out mutants but lost u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 76 publications
(91 reference statements)
6
57
2
Order By: Relevance
“…In the virions the viral genome is linear and double-stranded and no replication events occur. The presence of G4s at this level is compatible with the reported induction of G4s under molecular crowded conditions (53) and with the recently provided evidence that G4s are also present in post-mitotic DNA (21). …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the virions the viral genome is linear and double-stranded and no replication events occur. The presence of G4s at this level is compatible with the reported induction of G4s under molecular crowded conditions (53) and with the recently provided evidence that G4s are also present in post-mitotic DNA (21). …”
Section: Discussionsupporting
confidence: 91%
“…Attempts to characterize the DNA enriched for 1H6 binding sites have thus far been unsuccessful (8,21), however, since (i) the HSV-1 genome is extremely rich in G-rich regions that fold in G4 in vitro (17); (ii) a G4 ligand was able to suppress viral DNA replication and infectivity (17); (iii) ACV and PAA, compounds that selectively inhibit the viral DNA polymerase, decrease the amount of G4s in the infected cell (shown here); (iv) G4s in infected cells show striking virus cycle- and virus amount-dependence (shown here); (v) G4s in infected cells associate with viral RCs and are present in immature virions before and after budding at the nuclear membrane (shown here) convincingly indicate that the observed G4s are viral structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has since been demonstrated that ChlR1 is important for heterochromatin organization and that its depletion causes decreased chromatin compaction at pericentric and telomeric chromosomal regions (30). Furthermore, in vitro assays showed that the ChlR1 helicase efficiently unwinds DNA structures that contain G-quadruplex (G4) structures (31), which are frequently found in heterochromatin (32). This ability to resolve G4 structures that inevitably stall replication forks may help to explain why ChlR1-deficient cells are highly sensitive to DNA cross-linking agents, such as cisplatin and mitomycin C, that stall the replication machinery (33).…”
Section: Discussionmentioning
confidence: 99%